Retinal clinical and morphofunctional changes in high myopia in combination with age-related macular degeneration of different stages - L. K. Moshetova; I. B. Alekseev; I. V. Vorobyeva; Yu. A. Nam (Российский офтальмологический журнал, 2022)
Purpose: an analysis of clinical and morphofunctional changes of the retina in high myopia combined with age-related macular degeneration (AMD) of various stages.Materials and methods. We examined 45 patients (87 eyes, mean age 60 years) with high myopia (ave. spherical equivalent (SE) of refraction -11.0 D [-15.0; -7.125]) and the “dry” form of AMD, categories AREDS 1, 2, 3. Additionally, we formed three control groups of the same age range:  group 1 consisted of 30 healthy subjects (58 eyes) with a SE between -0.25 D and +0.5 D and no retinal changes; group 2 included 20 patients (38 eyes) with isolated high myopia (SE +0.5 D and no retinal changes; group 2 included 20 patients (38 eyes) with isolated high myopia (SE ³ 6.5 D) and group 3 included another 20 patients (36 eyes) with the “dry” AMD form (AREDS 2, 3). We evaluated the best corrected visual acuity (BCVA), indicators of retinal photosensitivity (MD, PSD) according to computer perimetry data, and morphological characteristics: central retinal thickness (CRT), the anteroposterior axis of the eyeball, the condition of the macular region of the retina according to optical coherence tomography (OCT) in the β-scan mode and autofluorescence (AF).Results: in case of the combined pathology, we detected a reliable reduction of average BCVA to the level of 0.5 [0.3; 0.7] (p < 0.001) and a reduced factor of retinal photosensitivity as compared to the control: MD to -4.36 dB (р<0.001), PSD to 2.97 dB (р < 0.001). CRT was 235 μm (p = 0.122), which showed no statistically significant differences to the control. Morphological changes of the retina corresponded to high myopia and AMD: a dome-shaped profile, lacquer cracks, paravascular retinal microcysts, paravascular lamellar ruptures; myopic maculopathy in the form of an epiretinal membrane, vitreomacular traction due to incomplete vitreoretinal cleavage, myopic foveoshisis; patchy chorioretinal atrophy, areas of diffuse RPE atrophy, damage of the junction line of the outer and inner segments of photoreceptors. The increase in the number and size of drusen depended on the stage of AMD. Normal autofluorescence of the fundus was absent. Pathological AF included minimal changes patterned as focal hypo- and hyperautofluorescence, reticular pattern, focal pattern, linear pattern, lace-like pattern, areas of geographic atrophy with pronounced hypoautofluorescence.Conclusion. Changes in OCT and visual field parameters (MD, PSD) in comorbid pathology (AMD combined with high myopia) were revealed. The morphofunctional indicators were compared for different AMD stages, and the diagnostic significance of AF was established.